Migrations and displacements: protect and welcome - Carrière, Jean Marie (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The Jesuit Refugee Service is concerned with accompanying, serving and defending refugees. It understands its action from below, from the proximity and the friendship with the refugees. It promotes fair policies of integration, based on the dignity of people and their suffering, and recognizes their rights as human beings. Within the complex phenomenon of global migrations bets on hospitality, especially at the local level.